Dysphagia Lusoria: A Case Report - F, Nik Qisti; Niza AS, Shahrun; R, Razrim (IIUM Medical Journal Malaysia, 2016)
Aberrant right subclavian artery is a rare cause of dysphagia. This is a congenital anomaly with the right subclavian artery originating from the dorsal part of the aortic arch and coursing through the mediastinum between the esophagus and the vertebral column. We report a case of a patient with chronic dysphagia caused by this condition. We further discuss the case with regards to its clinical features and options of management.